(untitled) (Ustozlar uchun, 2025)
Abstract: The COVID-19 pandemic reshaped the very foundation of English education worldwide. What was once dominated by traditional face-to-face classrooms suddenly shifted to virtual platforms, forcing teachers and learners to navigate an unfamiliar digital space. This dramatic change revealed both the fragility and the adaptability of the education system. While many students struggled with limited access to technology, unstable internet connections, and a lack of interactive engagement, others discovered new opportunities to learn beyond the classroom walls.